The extent of cost disclosure in trade company annual reports on the example of the IT branch: Pilot studies - Anna Dyhdalewicz (e-Finanse: Financial Internet Quarterly, 2014)
The paper presents the results of a research study, whose focal issue was the extent of disclosure in annual reports of costs of trade enterprises on the example of IT companies listed on the Warsaw Stock Exchange. Due to its limited scope, this study should be treated as a pilot, constituting the introduction to further and more detailed research and analyses, which ultimately will include all companies listed on the WSE within the Polish Classification of Activities (PKD) wholesale and retail trade, and car repair. The aim of the study is to evaluate the usefulness of the annual report as a source of information about the costs of a trading company. Information on costs in annual reports results from informational obligations defined by current regulations of law, environmental needs, as well as each economic entity's individual approach to the presentation of financial information in financial reports and to disclosure of additional information (qualitative and financial) in explanatory notes and in an activity report. It should also be noted that the presentation in the same costs group of different specific items proves that factors influencing the amount and structure of costs in a given period in particular entities conducting trading activity in the same sector have various significance for the results. Presenting information on risk within holdings indicates cost - determining factors both of operational and strategic natures, external and internal, dependent on the enterprise and independent of it. The sector in which the researched economic entities operate is an important factor which has an influence on the identification of cost drivers and costs whose source is risk related to the economic activity conducted.
Keywords: M41; 330; costs; trade companies in the IT branch; annual reports; cost-determining factors